2020
DOI: 10.2109/jcersj2.20013
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 〈111〉-oriented BaTiO<sub>3</sub> ceramics by high magnetic field electrophoretic deposition using hexagonal-tetragonal co-existing BaTiO<sub>3</sub> powder

Abstract: ©111ª-oriented BaTiO 3 (BT) ceramics were prepared by a high magnetic field assisted electrophoretic deposition method using hexagonal-tetragonal co-existing BT powders. With increasing the hexagonal content, the ©111ªorientation factor increased, while piezoelectric strain constant d 33 Ã increased up to the hexagonal content of 80% with attaining a maximum value of 627 pm V ¹1 and then rapidly decreased. In contrast, the decreasing trend of d 33 Ã with increasing hexagonal content in the randomly oriented ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…13,14 In order to enhance the piezoelectric properties, numerous strategies have been adopted such as sintering with new technology, modifying ceramics with dopants, or providing new ways to facilitate the poling process. [13][14][15][16][17][18][19] The ultrahigh piezoelectric effect is generally derived from the morphotropic phase boundary (MPB) in the BT-based system. 20 As BaTiO 3 has rich phase transition and unit cell structure types, the modication of BT to form MPB to improve piezoelectric performance is a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In order to enhance the piezoelectric properties, numerous strategies have been adopted such as sintering with new technology, modifying ceramics with dopants, or providing new ways to facilitate the poling process. [13][14][15][16][17][18][19] The ultrahigh piezoelectric effect is generally derived from the morphotropic phase boundary (MPB) in the BT-based system. 20 As BaTiO 3 has rich phase transition and unit cell structure types, the modication of BT to form MPB to improve piezoelectric performance is a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright © 2012 Springer Nature. BaTiO 3 , (BT) is a representative lead-free piezoelectric material that has been studied for a long time for the grain size effect [31][32][33][34], crystal structure at the atomic and electron level [35][36][37], nanoparticles [38][39][40], and texturing [41,42], and it is still being actively performed even to this day. Recently, Liu and Ren et al suggested in 2009 that Ca and Zr co-doped BT (BZT-BCT) has the potential to replace the PZT system [43].…”
Section: Lead-free Piezoelectricsmentioning
confidence: 99%
“…11,12) The widespread usage of MLCCs more or less relies on the defect chemistry [13][14][15][16][17][18][19][20][21] established for SrTiO 3 and BaTiO 3 . At present, intensive efforts [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have been made to explore nanostructured materials and devices using BaTiO 3 -based materials, whereas the deep understanding of defects is far from complete for Pb(Zr, Ti)O 3 , [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] (Bi, Na)TiO 3 , [54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%